Understanding artificial intelligence knowledge and usage among college students: Insights from a survey on classroom, coursework, and personal applications - basch, corey; Hillyer, Grace; Gold, Bailey; Yousaf, Helen (Review of Artificial Intelligence in Education, 2025)
Objective: This cross-sectional study involved distributing a survey to a sample of undergraduate college students AI-related knowledge, attitudes, and behaviors. Method: A total of 258 out of 319 college students enrolled in a personal wellness elective completed this survey during class. Results: Most participants (53.5%) reported familiarity with AI in general, often learning about it through the internet (79.1%). Participants who were frequent AI users more often said they were familiar with AI in general (62.3% vs. 47.1%, p = 0.04) and for educational purposes (52.3% vs. 34.8%, p = 0.02) and more frequently encountered AI information during class (42.5% vs. 23.9%, p = 0.002) compared with infrequent AI users. Frequent AI users more often agreed that AI makes learning easier (67.9% vs. 47.8%, p = 0.007), that AI use in school is ethical (27.2% vs. 8.1%, p<0.001), that AI improves writing skills (78.5% vs. 56.5%, p <0.001), improves critical thinking (36.2% vs. 19.7%, p =0.004), and improves interpersonal communication (38.3% vs. 24.8%, p = 0.035) compared to participants who less frequently used AI. Infrequent AI users more often agreed that using AI in class or for homework was cheating (56.6%, 25.2%, p <0.001), more often disagreed that they trusted AI as safe (51.1% vs. 26.2%, p <0.001), and more often turned to family and friends for information about AI (29.0% vs. 17.8%, p = 0.04) than frequent AI users. Conclusion: Research into the role of AI in education is still preliminary, but this work can serve as a foundation for future studies.